2021
DOI: 10.1002/mame.202100012
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium‐Embedded Polyhedral Oligomeric Silsesquioxane Containing Phosphaphenanthrene‐Substituent Group Used as Flame Retardants for Epoxy Resin Composites

Abstract: A zirconium hybrid polyhedral oligomeric silsesquioxane derivative (Zr-POSS-bisDOPO) is synthesized by the corner-capping and Kabachnik-Fields reactions. It is characterized by Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance spectroscopy (NMR), and then used as a flame retardant in diglycidyl ether of bisphenol A (DGEBA) to endow epoxy resin (EP) with flame retardancy. The flame retardancy, thermal stability, and mechanical properties of the cured EP/Zr-POSS-bisDOPO composites are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16] In addition to an enormous variety of CLMS nuclearities/molecular topologies, metallasilsesquioxanes are attractive candidates for applications in catalysis, [17][18][19][20] and designing new magnetic 21,22 or photoemissive materials. [23][24][25] In the context of materials chemistry, we could also mention the applicability of CLMSs to designing anodes for fast sodium storage, 26 flame retardants [27][28][29][30][31] and polyfunctional (SMM/luminescent) objects. 32 Surprisingly scarce information is available about manganese-based silsesquioxanes.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] In addition to an enormous variety of CLMS nuclearities/molecular topologies, metallasilsesquioxanes are attractive candidates for applications in catalysis, [17][18][19][20] and designing new magnetic 21,22 or photoemissive materials. [23][24][25] In the context of materials chemistry, we could also mention the applicability of CLMSs to designing anodes for fast sodium storage, 26 flame retardants [27][28][29][30][31] and polyfunctional (SMM/luminescent) objects. 32 Surprisingly scarce information is available about manganese-based silsesquioxanes.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, CLMSs offer an impressively wide scope of applications. These include the investigation of flame-retardant properties [ 25 , 26 , 27 , 28 , 29 , 30 ] and the development of approaches to anode [ 31 , 32 ] and ceramic [ 33 ] materials. Recent results revealed intriguing magnetic effects [ 34 , 35 ] (including the observation of spin glass [ 36 ] and single-molecule magnet [ 37 ] behaviors) and photophysical properties [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ] of CLMSs.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of partly condensed POSS is also appealing, leading to the design of new monomers for copolymerization reactions, H-bond donor catalysts, OLED’s emission layers, three-dimensional emulsifiers, different films (e.g., transparent, scratch resistant, self-healing, or Langmuir–Blodgett/Langmuir–Schaefer films), and spin-on-glass networks with ultralow dielectric constants . By design, partly condensed polyhedral silsesquioxanes can be also regarded as versatile ligands for the construction of various cagelike metallacomplexes. These intriguing compounds attract significant interest for the potential removal of radioactive elements, fabrication of flame retardants, biomedical agents, luminescent materials, , or molecular magnets . Magnetic studies revealed rare cases of single-molecule magnets (SMMs), , spin glass, or spin–flip transition effects.…”
Section: Introductionmentioning
confidence: 99%